The Effect of Different Surface Treatments on the Color Stabilities of Lithium Disilicate Material - Onur Doğan Dağ; Göknil Alkan Demetoğlu; Ayşegül Kurt (Selcuk Dental Journal)
Background: The aim of this study is to investigate the clinical acceptability of the color change that may occur in time about full ceramic materials used for aesthetic restorations, which are bonded after different surface conditioning processes, by measuring with spectrophotometer. Methods: The lithium disilicate CAD material we used in our work was prepared with isomet in the form of 1-millimeter-thick specimens. Three random groups of 21 specimens were selected from the specimens. One of these groups was conditioned with phosphoric acid, which is recommended by the manufacturer. Er:YAG laser was applied to the second group. The third group was conditioned by Nd:YAG laser. Surface changes in the groups were evaluated by scanning electron microscope (SEM) and atomic force microscope (AFM). The specimens were bonded with the adhesive resin cement to the background material for color change measurement. The first color measurement of the bonded specimens was done by spectrophotometer. The specimens were aged at 10,000 cycles in the thermal cycle device. The second color measurement after aging was done with the same spectrophotometer. Results: After aging with thermal cycle, there was a clinically acceptable color change in all groups. The Nd:YAG laser group presented better color stability (p